Odor-Active Compounds in Cooked Rice Cultivars from Camargue (France) Analyzed by GC−O and GC−MS - Maraval, Isabelle; Mestres, Christian; Pernin, Karine; Ribeyre, Fabienne; Boulanger, Renaud; Guichard, Elisabeth; Gunata, Ziya (Journal of agricultural and food chemistry, 2008)
Volatile compounds of cooked rice from scented (Aychade, Fidji) and nonscented (Ruille) cultivars grown in the Camargue area in France were compared to that of a marketed Asian scented one (Thai) by gas chromatography−olfactometry (GC−O) and gas chromatography−mass spectrometry (GC−MS). GC−O analyses of the organic extracts resulted in the perception of 40 odorous compounds. Only two compounds, oct-1-en-3-one and 2-acetyl-1-pyrroline, were almost always perceived. Hierarchical cluster analysis showed that most of the difference between rice odors was linked to quantitative differences with only 11 compounds being specific to some of the rice. Sixty compounds were identified and quantified by GC−MS, including a few new odor-active components. Principal component analysis enabled us to differentiate scented cultivars from a nonscented one, and scented rice cultivars from Camargue from a Thai sample. Calculated odor-active values evidenced that the Thai sample odor differed from that of scented Camargue cultivars because of the degradation of lipids and of cinnamic acid compounds.